Fungal recognition by mammalian fibrinogen‐related proteins. (30th September 2020) - Pilecki, Bartosz; Moeller, Jesper Bonnet
Abstract: Fungi are ubiquitous eukaryotic micro‐organisms present in virtually all environmental habitats. Although rarely pathogenic to the healthy population, many fungal species are capable of causing human disease in immunocompromised individuals. Thus, fungal infections remain a significant cause of morbidity and mortality, with rising prevalence accompanying the worldwide increase in immunosuppression‐based therapies. Therefore, better understanding of the mutual interactions between the protective host mechanisms and the invading fungi remains of critical importance. The innate immune system constitutes the first line of defence against exogenous insults. The innate antifungal immunity is mediated through recognition of specific pathogen‐associated molecular patterns (PAMPs) by a broad panel of host pattern recognition receptors (PRRs), responsible for mounting adequate protective responses. In this review, we describe fungal PAMPs as well as a selection of PRRs able to recognize them. We focus on the members of the fibrinogen‐related domain (FReD) protein family that have been shown to recognize fungi‐derived molecules: ficolins, fibrinogen C domain containing 1 (FIBCD1) and tenascin‐C. We describe their structure, their binding targets and their established as well as putative biological functions related to fungal recognition and immunity.